Association between grip strength, walking pace and incident peripheral artery disease: A prospective study of 430,886 UK biobank participants - Duqiu Liu; Chenxing Yang; Gang Liu; Tianyu Guo; Sen Liu; Yi Guo; Jinjie Xiong; Ru Chen; Shan Deng (International Journal of Cardiology. Cardiovascular Risk and Prevention)
Background and aims: Patients with peripheral artery disease (PAD) presented overall muscle weakness and reduced physical performance. Previous study focused on the impact of muscle weakness on outcomes of established PAD, however the relationship between compromised muscle function and incident PAD remained unclear. Methods: A prospective study involving 430,886 participants aged 40–69 y from UK biobank was conducted. The main outcome was incident PAD. Grip strength and walking pace were used as indicators for muscle function. Grip strength was measured using a Jamar J00105 hydraulic hand dynamometer, while walking pace was self-reported by the participants. Cox proportional hazard models were employed to investigate the relationship between grip strength, walking pace, and incident PAD. Results: A total of 430,886 individuals were included in the final analysis. The mean age of the participants were 56.44 years, and 55.3 % were female. Over a median follow-up period of 13.81 years, 5,661 participants developed PAD. Higher grip strength, whether absolute or relative, exhibited a dose-dependent inverse association with incident PAD. Each 1 kg increment in absolute grip strength and each 0.01 kg/kg increase in relative grip strength were associated with reduced PAD risk by 2 % (HR: 0.98; 95 % CI [0.97–0.98]) and 83 % (HR: 0.17; 95 % CI [0.13–0.23]), respectively. Slow walking pace significantly correlated with increased PAD risk, while brisk walking pace was associated with decreased PAD risk. Conclusion: Absolute grip strength, relative grip strength and walking pace were inversely associated with the risk of incident PAD.